TINGKAT MOTIVASI PETANI DALAM BETERNAK SAPI DI KECAMATAN SAMBAS KABUPATEN SAMBAS - Harmoko 2017 (University of Jember, 2017)
Farmers as cattle ranchers, the impetus for raising cows can provide benefits. In addition to the results from farming, cattle results can be used as a